HLA-DRB1 typing of Vogt-Koyanagi-Harada's disease by PCR-RFLP and the strong association with DRB1*0405 and DRB1*0410. Issue 3 (March 1994) - Shindo, Y; Inoko, H; Yamamoto, T; Ohno, S
Abstract : Vogt-Koyanagi-Harada's (VKH) disease is reported to be closely associated with the HLA class II antigen, HLA-DR4. Serologically defined DR4 is further divided into 11 alleles by molecular HLA genotyping. However, no study of HLA-DNA typing of VKH patients has been reported. To clarify molecular genetic mechanism underlying the susceptibility/resistance to VKH disease, HLA-DNA typing of DR antigens (DRB1 genotyping) by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was performed. It was found that DRB1*0405 showed a significant association with VKH disease compared with the healthy controls (corrected p value < 1 x 10(-5)) and that all the patients had DRB1*0405 and/or DRB1*0410. The specific amino acid residue shared only by these two alleles is Ser at position 57 which is located in the antigen binding groove and may influence the immunological function as an antigen-presenting molecule, suggesting that Ser at position 57 plays an important role in the susceptibility to VKH disease, although the possibility that the involvement of the HLA-DQ molecule, DQ4, in strong linkage disequilibrium with DRB1*0405 and DRB1*0410, cannot be excluded.